2019
DOI: 10.1080/15384101.2019.1676584
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of RNA editing reveals new insights into the dynamic gene regulation of spermatogenesis

Abstract: Spermatogenesis is an important physiological process associated with male infertility. As a kind of post-transcriptional regulation, RNA editings (REs) change the genetic information at the mRNA level. But whether there are REs and what's the role of REs during the process are still unclear. In this study, we integrated published RNA-Seq datasets and established a landscape of RNA REs during the development of mouse spermatogenesis. Totally, 7530 editing sites occurred in 2012 genes among all types of male ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Some RNA editing events are tissue specific ( Tao et al, 2012 ), but the available knowledge about RNA editing in gonads is very limited. In mouse testis, adar1 and adar2 genes are expressed in both Sertoli cells and the germline in a cell-type-dependent manner during germ cell development ( Snyder et al, 2017 ), and 2012 genes exhibiting editing events in germ cells during spermatogenesis have been detected ( Wang et al, 2019 ). However, the functions of RNA editing in gonads are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Some RNA editing events are tissue specific ( Tao et al, 2012 ), but the available knowledge about RNA editing in gonads is very limited. In mouse testis, adar1 and adar2 genes are expressed in both Sertoli cells and the germline in a cell-type-dependent manner during germ cell development ( Snyder et al, 2017 ), and 2012 genes exhibiting editing events in germ cells during spermatogenesis have been detected ( Wang et al, 2019 ). However, the functions of RNA editing in gonads are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond mutations to genetic sequences, RNA editing is another factor associated with various diseases, as the process affects gene translation into proteins. Chromosome 17 and both ends of chromosome Y are more enriched in RNA editing sites than other chromosomes in all types of male germ cells (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Beyond mutations to genetic sequences, RNA editing is another factor associated with various diseases, as the process affects gene translation into proteins. Chromosome 17 and both ends of chromosome Y are more enriched in RNA editing sites than other chromosomes in all types of male germ cells (Wang et al, 2019). Screening for genes associated with sperm quality revealed that teratozoospermia‐associated and testis‐specific genes are mostly distributed in chromosomes 17 and 19 (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to explore the function of RNA editing response to different biological processes. Accordingly, numerous studies have reported that RNA editing is associated with brain development [23], spermatogenesis [24], cancer development, and metabolic disorders [25]. In light of this that millions of editing sites have been identified in domesticated animals, like sheep [26], bovines [27], chicken [28], and pig [29], etc.…”
Section: Introductionmentioning
confidence: 99%